Different reverse remodelling between left ventricle and right ventricle in fulminant heart failure due to giant cell myocarditis: a case report. Issue 8 (23rd August 2021) - Yokoyama, Hiroaki; Yamaguchi, Masashi; Tobita, Kazuki; Saito, Shigeru
Abstract: Background: Giant cell myocarditis (GCM) is a rare cause of fulminant heart failure (HF). The most common presentation is progressive hemodynamic deterioration, and a few cases present with idiopathic complete atrioventricular block (cAVB). The prognosis of GCM is poor, and GCM patients usually die of HF and ventricular arrhythmia unless cardiac transplantation is performed. Few reports have described the effects of treatments such as immunosuppression and detailed reverse remodelling in GCM patients. Case summary: A 69-year-old female presented with cAVB. Transvenous pacemaker was implanted via the left subclavian vein. One and a half months later, she exhibited left ventricular dyssynchrony and lower left ventricular ejection fraction (LVEF), resulting in hospitalization for HF. She received cardiac resynchronization therapy; however, this had no apparently positive effects on her cardiac function. To investigate the cause of the lower LVEF, an endomyocardial biopsy was taken from the right ventricular septum. She was diagnosed with GCM and immediately received immunosuppression therapy with prednisolone and ciclosporin. This resulted in the functional recovery of the right ventricle; on the other hand, the left ventricle had still not recovered based on transthoracic echocardiography. Fortunately, she successfully recovered from severe HF without recurrence. Discussion: This is a case of fulminant HF due to GCM which initially presented as cAVB. Moreover, this case demonstrates the quite difference of the functional recovery between the left ventricle and the right ventricle with immunosuppression therapy.